Measurement sustainability: A first methodological step for its modeling and assessment. (15th March 2023) - Angrisani, Leopoldo; Arpaia, Pasquale; D'Arco, Mauro; De Benedetto, Egidio; Esposito, Antonio; Imbó, Monica; Tedesco, Annarita
Abstract: Sustainability has gained significant relevance in every sector. In particular, in information and communication technology (ICT), there is growing attention towards this aspect. Measurement systems are arguably one of the numerous manifestations of ICTs, and they are virtually ubiquitous in the current 4.0 Era. This pervasiveness leads to ponder over the effect that measurement systems have on the environment. However, to date, no study addressed the sustainability of measurements and their impact on the environment. This work proposes a first methodological approach for the modeling and assessment of environmental sustainability of measurements as part of ICT. In particular, an iterative approach is presented to assess the impacts of the measurement as a whole. This also paves the way to unveil the relation between measurement sustainability and measurement uncertainty. As representative examples, in this work, two practical scenarios are considered: (i) measurement of resistances with a Wheatstone bridge and (ii) measurement of emissions from an internal combustion engine. Graphical abstract: Highlights: A methodological approach is proposed for assessing measurement sustainability. An iterative approach is presented to assess the impacts of the measurement. Two case studies are presented. First, the uncertainty–sustainability trade-off is investigated for a Wheatstone bridge. Second, the impact of measuring emissions from an internal combustion engine is calculated.